Análisis de los esfuerzos mecánicos generados en las articulaciones de rodilla y cadera durante la trayectoria total de la marcha humana (2015)
This article describes a finite element analysis of hip and knee joints in the stance phase of human gait. At first, geometric 3D models of hip and knee joint were obtained; the forces produced by the main muscles that affect directly hip and knee joints were registered with OpenSim, in order to determine the total moments and forces generated in the joints through the human gait. Boundary conditions, points of application of forces, moments and fixed supports were defined and simulations were developed during the stance phase. Maximum stresses during the stance phase were determined with the results obtained with the application of ANSYS.